The effects of recreational programs on the maintenance of some elements of physical fitness for the players of Dijlah Sports Club in the transition phase (Texas Journal of Multidisciplinary Studies, 2024)
The research aimed at the impact of recreational programs in maintaining some elements of physical fitness for the players of the Dijlah Sports Club for the transitional stage, and the researcher used the experimental method to suit the nature of the research, and research community and sample was from the players of the Dijlah Sports Club in Maysan Governorate for the academic year (2023/2024) and the researcher apply the recreational program from 1/6/2023 to 2/8/2023, where the total period of implementing the program (two months) and the total number of units (16) units, two units per week and the unit time (40-60) minutes, and researcher used appropriate statistical methods, The researcher presented and analyzed the results and discussed them from the use of its own table and there are statistically significant differences between the premeasurement and measurement in some elements of physical fitness in favor of the postmeasurement and then the researcher wrote the conclusions and this indicates the effect of the recreational program on maintaining some elements of physical fitness for the players of the Degla Sports Club and the most important recommendations to generalize the results of the tests to the clubs that the research was conducted in order to benefit from them, not to neglect the transition phase in the players and the need to pay attention to them.